Garlic tablet supplementation reduces lipopolysaccharide-induced TNF-alpha production by peripheral blood mononuclear cells. (December 2016) - Mahdavi-Roshan, Marjan; Rismanchi, Marjan; Nasrollahzadeh, Javad
This study was designed to investigate whether garlic tablets possess anti-inflammatory and lipid-lowering effects in healthy adults. Twelve healthy adults participated in a randomized, cross-over design with a three-week treatment and a two-week washout period. Participants received either garlic powder tablets twice daily or two placebo tablets/day for three weeks. Plasma and peripheral blood mononuclear cells (PBMC) were isolated from fasting blood samples at baseline and after each three-week treatment with garlic or placebo. PBMC were cultured, stimulated with lipopolysaccharide (LPS), and changes in cell culture supernatants tumor necrosis factor-α (TNF-α) levels were determined. In addition, changes in plasma high-sensitivity C-reactive protein (hs-CRP), as well as plasma levels of lipids were determined. After three weeks of supplementation, LPS-stimulated TNF-α release in cell culture supernatant was lower after garlic than placebo ( P <0.05) whereas no significant changes were observed in unstimulated TNF-α release or plasma TNF-α. There were no significant differences in plasma hs-CRP, cholesterol, triglyceride, LDL cholesterol, and HDL cholesterol levels between garlic and placebo. In healthy individuals, garlic supplementation did not change plasma levels of TNF-α and hs-CRP while it caused lower TNF-α release into cell culture supernatant after stimulation by LPS.